The question of primary school social purpose in the beginning of 19th century in Lithuania - Lukšienė, M. (Psichologija, 1966)
The article is written based mostly on the archive materials and reviews one of the major episodes in educational history in the beginning of 19th century in Lithuania: feudal cast seeks to restrict and to steer into desired direction a growing need for education in the period of development of mass consciousness.In the beginning of 19th century Lithuanian people shows much initiative in the field of education: the number of village schools in mother tongue and the number of students is growing, and the number of peasant children in some schools account for about a half of the students, for example in the western part of Lithuania.Despite the difficult social conditions in feudal period, the cast of intelligentsia form gradually. Eventually, it becomes the major participant of creative process of Lithuanian democratic culture.The desire of mass education sets three directions of education. The extreme reactional groups in feudal cast view peasants exceptionally as a work force which needs religious teachings without elementary basic knowledge. The liberal aristocracy places focus on greater work efficacy that is reached by educated worker. Thus the representatives of this approach proposed the implementation of professional education in peasant elementary schools. Representatives of the third approach believed that masses need free admission to all schools without any restrictions.
Keywords: primary school; history of pedagogics